Dc electrical properties of semiconducting cobalt oxide substituted lead vanadate glasses - K. Brahmananda Rao, K.; V. Ramesh, K.; Tejeswara Rao, P. (International Journal of Engineering and Technology, 2018)
Semiconducting lead vanadate glasses with CoO substitution represented as xCoO-(50-x) PbO-50V2O5 with x=5,10 and 15 mol% were prepared by melt quenching technique. They were characterized by X-ray diffraction (XRD), Scanning electron microscopy (SEM), differential thermal analysis (DTA) and DC electrical conductivity. The overall features of these XRD curves reveal the amorphous nature of present glasses. SEM investigations were conducted for the micro structural characterization of V2O5 crystal phases. Density was observed to decrease with an increase in CoO content. The dc electrical conductivity of the present system increases as the concentration of substitution of CoO increases with 5molpercentage to 15molpercentage.Â Â